2018
DOI: 10.1016/j.tcs.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Leaf realization problem, caterpillar graphs and prefix normal words

Abstract: Given a simple graph G with n vertices and a natural number i ≤ n, let L G (i) be the maximum number of leaves that can be realized by an induced subtree T of G with i vertices. We introduce a problem that we call the leaf realization problem, which consists in deciding whether, for a given sequence of n+1 natural numbers ( 0 , 1 , . . . , n ), there exists a simple graph G with n vertices such that i = L G (i) for i = 0, 1, . . . , n. We present basic observations on the structure of these sequences for gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Cicalese et al gave a generation algorithm in [15], with linear running time per word, and studied infinite prefix normal words in [16]. Prefix normal words and prefix normal forms have been applied to a certain family of graphs by Blondin-Massé et al [7], and were shown to pertain to a new class of languages connected to the Reflected Binary Gray Code by Sawada et al [29]. Very recently, Fleischmann et al presented some results on the size of the equivalence classes in [?…”
Section: Related Workmentioning
confidence: 99%
“…Cicalese et al gave a generation algorithm in [15], with linear running time per word, and studied infinite prefix normal words in [16]. Prefix normal words and prefix normal forms have been applied to a certain family of graphs by Blondin-Massé et al [7], and were shown to pertain to a new class of languages connected to the Reflected Binary Gray Code by Sawada et al [29]. Very recently, Fleischmann et al presented some results on the size of the equivalence classes in [?…”
Section: Related Workmentioning
confidence: 99%
“…In particular, since they have a linear structure, they might be interpreted as words embedded in graphs. For instance, in [3], the second author of this article and his co-authors established a link between the leaf function of caterpillar graphs and prexnormal words, a family of words closely related to the bubble sort [7].…”
Section: Introductionmentioning
confidence: 99%
“…Prefix normal words were introduced by G. Fici and Z. Lipták in [4] because of their connection to binary jumbled pattern matching. Recently, prefix normal words have been used because of their connection to trees with a prescribed number of vertices and leaves in caterpillar graphs [6].…”
Section: Introductionmentioning
confidence: 99%